Inorganic and organic nitrogen uptake by nine dominant subtropical tree species - Li C; Li Q; Qiao N; Xu X; Li Q; Wang H (iForest - Biogeosciences and Forestry, 2016)
We explored inorganic and organic N uptake patterns by dominant tree species in a subtropical plantation of southern China to improve understanding of nitrogen (N) cycling in these forests. We labeled intact roots by brief 15N exposures in field hydroponic experiments. Nine dominant tree species were examined to compare the effects of functional plant group (conifers versus broadleaves), mycorrhizal types, and forest successional stages on N uptake. All investigated species took up glycine at lower rates than other N forms, with mean values of 2.55 ± 0.36 µg N g-1 d.w. root h-1. Nitrate uptake rates for all species (average 5.81 ± 0.35 µg N g-1 d.w. root h-1) were significantly lower than ammonium (36.86 ± 5.17 µg N g-1 d.w. root h-1). All investigated species absorbed ammonium for more than 80% of total N uptake. Nitrate acquisition by these species was about 14% of total N uptake, with only 6% for glycine. Conifers showed significantly higher uptake rates of glycine, but lower uptake of nitrate than broadleaves. Arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) tree species showed significant difference in nitrate uptake, with higher rates by AM tree species. Tree species at late-successional forest stages showed higher uptake rates of nitrate than those in earlier successional stages. Our findings indicate that ammonium is the dominant N source and glycine is a minor N source throughout forest succession.